A second look at inference for bivariate Skellam distributions. Issue 1 (16th February 2017) - Aissaoui, Sidi Allal; Genest, Christian; Mesfioui, Mhamed
Abstract : Two bivariate extensions of the Skellam distribution were introduced in 2014 by a subset of the present authors, who also proposed moment estimators for the dependence parameters in these models. The limiting distribution of these estimators is established here, and their asymptotic efficiency is compared with that of the corresponding maximum likelihood estimators. © 2017 The Authors. Stat Published by John Wiley & Sons Ltd.